ANALISIS AKTA PERDAMAIAN SENGKETA EKONOMI SYARIAH DI PENGADILAN AGAMA SRAGEN DI TINJAU DARI AL-SHULHU DAN PERMA NO. 1 TAHUN 2016 TENTANG PROSEDUR MEDIASI DI PENGADILAN - Puji Rahayu, Fadilah Qotimatun (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2020)
ABSTRACT In this issue, the authors formulated the problem of sharia economic dispute settlement in the Decision Number 1479 / Pdt.G / 2019 / PA.Sr and Decision Number 1480 / Pdt.G / 2019 / PA.Sr and how the Analysis of the Peace Certificate of Sharia Economic Disputes in the Religious Courts Sragen is reviewed from Al-Shulhu and Perma No. 1 of 2016 concerning Mediation Procedures in the Court. This research is a library research. Data collection conducted by Decision Number 1479 / Pdt.G / 2019 / PA.Sr and Decision Number 1480 / Pdt.G / 2019 / PA.Sr with supporting data in the form of interviews with Religious Court judges Sragen and documentation. Data analysis in this research was conducted by discourse analysis or discourses analysis method. This research shows that the resolution of Islamic economic disputes in these two articles is in accordance with the rules using legal sources from the Penal Code, Article 130 HIR, Perma No. 1 of 2016 concerning Mediation Procedures in Courts and Statutes No.4 of 2019 concerning Procedures for the Settlement of Simple Lawsuit. Reviewed by using al-shulhu and Perma No. 1 of 2016 concerning Mediation Procedures in the Court is in accordance with the principles of as - Shulhu and the provisions in Perma No. 1 of 2016 concerning Mediation Procedures in the Court. Keywords: Al-shulhu; PERMA No. 1 of 2016; Sharia Economic Case. ABSTRAK Dalam permasalahan ini, penulis merumuskan permasalahan penyelesaian sengketa ekonomi syariah pada Putusan Nomor 1479/Pdt.G/2019/PA.Sr dan Putusan Nomor 1480/Pdt.G/2019/PA.Sr serta bagaimana Analisis Akta Perdamaian Sengketa Ekonomi Syariah di Pengadilan Agama Sragen di Tinjau dari Al-Shulhu dan Perma No. 1 Tahun 2016 Tentang Prosedur Mediasi di Pengadilan. Penelitian ini merupakan penelitian kepustakaan (Library Research). Pengumpulan data yang dilakukan dengan Putusan Nomor 1479/Pdt.G/2019/PA.Sr dan Putusan Nomor 1480/Pdt.G/2019/PA.Sr dengan dilakukan data pendukung berupa wawancara hakim Pengadilan Agama Sragen dan dokumentasi. Analisis data dalam penelitian ini dilakukan dengan metode analisis wacana. Penelitian ini menunjukan bahwa penyelesaian sengketa ekonomi syariah dalam kedua Putusan sudah sesuai aturan dengan menggunakan sumber hukum dari KUHPerdata, Pasal 130 HIR, Perma No. 1 Tahun 2016 tentang Prosedur Mediasi di Pengadilan dan Perma No. 4 Tahun 2019 Tentang Tata Cara Penyelesaian Gugatan Sederhana. Ditinjau dengan menggunakan as-shulhu dan Perma No. 1 Tahun 2016 tentang Prosedur Mediasi di Pengadilan sudah sesuai dengan prinsip as-Shulhu dan ketentuan dalam Perma No. 1 Tahun 2016 tentang Prosedur Mediasi di Pengadilan. Kata Kunci: As-shulhu; Perkara Ekonomi Syariah; PERMA No. 1 Tahun 2016.